Tinjauan terhadap Pendistribusian Zakat Profesi dalam Peningkatan Kesejahteraan Masyarakat ( Studi pada BAZNAS Kab. Maros) - Mujahidin Mujahidin (Al-Tijary, 2019)
This study aims to analyze the National Zakat Amil Agency (BAZNAS) of Maros Regency in distributing zakat. The research design is field research and uses qualitative descriptive methods. The instruments of this study are interview guides, field notes and recoding. The results of the study found that: 1) BAZNAS Maros district distributes zakat in Consumptive and productive forms. 2) consumptive is given once in a while which is carried out in the month of Ramadan except for study completion assistance when given a request to enter through a proposal for study completion assistance, while for productive funds is channeled every three months based on incoming requests for assistance.